Towards a 2025 Global Beer Market: The Use of Aptamers in Biosensors to Detect Acetobacter Aceti in Beer - A Biotechnological Approach to Improve Food Hygiene and Safety in Beer Developing Markets and Beyond (IPS Journal of Nutrition and Food Science, 2024)
Aptamers were studied to see if they could be designed as a rapid detector for viable spoilage organisms in beer. SELEX was used to obtain aptamers from random libraries of oligonucleotides that could bind to A. aceti. 13 SELEX rounds were performed to get specific aptamers, whole and counter cell-SELEX was employed. Aptamers’ binding ability to A. aceti was tested by flow cytometry and confirmed to bind by synthesizing them with fluorescent labels (5’FAM). ANOVA and a one-sample test revealed significant difference in the binding ability of selected aptamers (P < 0.05). A12 and A10 showed the highest fluorescent intensity (180 and 150) for binding ability. Flow cytometry test for the binding specificity of aptamers and their truncated sequence in comparison with other organisms revealed selected aptamers to be specific to A. aceti cells having the highest mean fluorescence intensity values of 120 ± 3.8 (A12), 119 ± 5.2 (TA12), 110 ± 4.5 (A10) and 111 ± 6.2 (TA10). The best predicted folding structure of selected aptamers from mFold was determined from the Gibbs free energy (A10: ΔG = -4.40, TA10: ΔG = 0.07, A12: ΔG = - 4.96, TA12: ΔG = 0.43). Sigmaplot showed no dose-dependent relationship for detection in candidate aptamers. A12 had a low KD value of 11.22 ± 1.32 nM which further validated it as the best aptamer for detecting A. aceti in beer.
Keywords: Aptamers; Aptasensors and biosensors; Oligonucleotides; Beer; Spoilage organisms; Acetobacter aceti in beer; Food hygiene; Food safety; Rapid detection and high throughput techniques; Developing beer markets